Quantification of solution annealing effects on microstructure and property in a laser powder bed fusion 316H stainless steel - Lin Gao; Srinivas Aditya Mantri; Xuan Zhang (Materials & Design)
Solution annealing (SA) is an effective way to mitigate microstructural heterogeneity and to optimize mechanical performance of alloys manufactured by laser powder bed fusion (LPBF). In this study, a comprehensive and quantitative understanding of the recovery and recrystallization processes in the SA temperature range of LPBF 316H stainless steel is provided using results from analytical electron microscopy and in-situ high-energy synchrotron x-ray scattering. The profound effect of dislocation structures and secondary phase particles on mechanical performance, particularly under tension and creep conditions, is rationalized using deformation models that incorporate microstructural inputs. This study, for the first time, quantifies the broad effect of nano oxide inclusions on dislocation recovery kinetics, on grain growth and recrystallization kinetics, and on tension strength and creep resistance. The fundamental differences between the LPBF and the conventional wrought materials are revealed. The findings address critical questions in post-build processing of AM materials and pave the way for their rapid qualification for high temperature applications.